Literasi Kesehatan: Pemberdayaan Sekaa Teruna Teruni dalam Penanganan Kegawatdaruratan Pre-Hospital - Agustini, Ni Luh Putu Inca Buntari; Wahyunadi, Ni Made Dewi; Yusniawati, Yustina Ni Putu; Sanjana, I Wayan Edi; Dewi, Ni Putu Ayu Ratna; Putra, Komang Ardidhana Nugraha; Wijayantha, I Putu Arya; Wardana, Dewa Gede Wisnu (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Background: Lay people are the first and main helpers for victims who experience emergencies outside the hospital. However, facts on the ground show that people are often confused about providing assistance to victims at the scene and tend to wait for the medical team, thereby missing the